(3efjI GdeMUdjf aj MbjI WQjbI GdeLJgOjfs - (3GdMSjfj, GdcGXej, oTnqHQ, GdeLdSj GdKGfj, YHO Gddg Hf eMeO QVG Bd THQ, J (B1242(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj CLeYJ GdYUGHI Ydi JbOS PGJg(B...(3CeG HYO(B... (3gPg QSGdI JTJed Ydi eSGFd UGQJ eMdG ddNdGa(B...s
(3BNQgG (B:s
(3eHJhQI GdBNQ, hBNQ GdehLhO efgG(B: ... (3hjSJaGO ef cdGe GdUOhb QMeg Gddg aj Gdabjg aEfg QMeg Gddg YqO aj Chd GdcJGH CMGOjKg UMjMI(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B4(3,U(B131s
(3GdPQjYI(B:(3L(B23(3,U(B208(3,Qbe(B8655s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds